THE IMPACT OF VATICAN II ON THE IDENTITY OF THE CHURCH IN AFRICA: The African Synods in Comparative Perspective - Carey, Tim (Asian Horizons, 2013)
The African Synods – the first in 1994 and the second in 2009 – aimed to highlight some of the basic issues facing the mission and nature of the Catholic Church in Africa. While the former synod characterized the ministry of the African church through the model of family in God, the latest synod was charged with developing a model which promoted the themes of reconciliation, peace, and justice in light of regional conflicts arising within many sub-Saharan African countries. Bringing together bishops and church leaders from throughout the continent, the synods were motivated by the need for an articulation of the presence and activity of the Catholic Church in Africa in the period of post-colonial independence especially after the 1994 Rwandan genocide and South Africa’s Truth and Reconciliation Commission in 1995.